THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING APPROACH AND ACHIEVEMENT MOTIVATION UPON STUDENTS' WRITING COMPETENCY FOR THE TENTH GRADE STUDENTS OF SMAN 1 KERUAK IN THE ACADEMIC YEAR 2012-2013 - ., LALU SUPARMAN; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Prof. Dr. Nyoman Dantes (Universitas Pendidikan Ganesha, 2013)
This research aims at investigating the effect of contextual teaching and learning approach and achievement motivation upon studentsâ?? English writing competency. The population of this study was the students of grade ten in SMA Negeri 1 Keruak. The numbers of the population were 227 students, where 88 students were selected to be the sample. It was an experimental study of posttest-only control group with 2x2 factorial design in which the treatement lasted from October 2012 until December 2012.The data of students' writing competency in this study were analyzed using Two-way ANOVA and Tukey test, meanwhile the data collection were collected through achievement motivation questionnaire and writing competency test.The findings of the research are (1) students taught using contextual teaching and learning approach can significantly achieve better in writing than those taught by using conventional approach, (2) there is a significant interaction between contextual teaching and learning approach and achievement motivation upon studentsâ?? writing competency, (3) for students with high achievement motivation, studentsâ?? taught using contextual teaching and learning approach achieved significantly better than those who were taught using conventional approach, (4) for studentsâ?? with low achievement motivation, there is a significant difference between the students who taught using contextual teaching and learning approach and those who taught using conventional approach.keyword : contextual teaching and learning approach, achievement motivation, and writing competency